FeSiAl magnetic powder core with high magnetic conductivity and low loss as well as preparation method and application of FeSiAl magnetic powder core

By using a coating and bonding slurry prepared from low-melting-point Al powder and organosilicon sol, an alumina-SiO2 composite insulating layer is formed, which solves the problems of eddy current loss and permeability of FeSiAl magnetic powder cores in high-frequency applications and achieves the effect of high permeability and low loss.

CN121506667AActive Publication Date: 2026-02-10广东泛瑞新材料股份有限公司

Patent Information

Application Number
CN202511792117.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-01
Publication Date
2026-02-10
Estimated Expiration
2045-12-01

AI Technical Summary

Technical Problem

Existing technologies struggle to effectively reduce eddy current losses and improve permeability of FeSiAl magnetic powder cores while maintaining good adhesion and high-temperature resistance. This is especially true in high-frequency applications, where commonly used low-melting-point glass powders lead to magnetic dilution effects and poor interfacial compatibility, impacting the coating effect.

Method used

A coating adhesive slurry is prepared by using low-melting-point pure Al powder with organosilicon sol, aluminate coupling agent, lubricant and organic binder. The slurry is then cured and sintered under vacuum to form a uniform alumina-SiO2 composite insulating coating layer. The Al powder is melted at high temperature to fill the air gap and oxidized in situ to form a stable insulating layer.

Benefits of technology

It significantly improves the density and insulation coating effect of magnetic powder cores, reduces magnetic dilution effect, increases magnetic permeability and reduces high-frequency loss, and enhances the high-temperature stability of materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of soft magnetic materials, and particularly relates to a high-permeability low-loss FeSiAl magnetic powder core and a preparation method and application thereof. The preparation method comprises the following steps: (1) uniformly mixing pure Al powder with organic silica sol, an aluminate coupling agent, a lubricant and an organic binder to obtain coated bonding slurry; and (2) uniformly mixing FeSiAl soft magnetic powder with the coating and bonding slurry obtained in the step (1), carrying out hot-pressing curing molding at the temperature of 60-100 DEG C under a vacuum condition, and then carrying out hot-pressing sintering treatment at the temperature of 750-1000 DEG C under an oxygen-containing atmosphere condition to obtain the FeSiAl magnetic powder core with high magnetic conductivity and low loss. The FeSiAl soft magnetic powder is subjected to insulation coating and bonding treatment by adopting the coating and bonding slurry with specific composition, the high-frequency loss of the obtained magnetic powder core can be reduced by combining a specific treatment process, and the influence on the magnetic conductivity is relatively small.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of soft magnetic materials, and particularly relates to a high-permeability low-loss FeSiAl magnetic powder core and a preparation method and application thereof. BACKGROUND

[0002] The magnetic powder core is a kind of soft magnetic composite material manufactured by a powder metallurgy process, has good comprehensive performance, and is widely applied to various electronic components such as communication, energy, automobile industry, filter, mutual inductor and the like. With the development of electronic products in the direction of miniaturization, high frequency, energy saving and high sensitivity, the magnetic powder core is required to have high permeability, high magnetic property stability, high saturation magnetic induction strength and low loss.

[0003] The FeSiAl soft magnetic alloy refers to a high-permeability soft magnetic alloy with FeSiAl as a main component element, and is also called sendust alloy. The alloy has the remarkable features of a magnetic anisotropy coefficient close to zero and a saturation magnetic hysteresis coefficient close to zero. Compared with other soft magnetic alloy materials, the FeSiAl soft magnetic alloy material has the comprehensive advantages of low loss, high resistance, low cost and no noise, and is favored.

[0004] The FeSiAl magnetic core is mainly applied to the high-frequency field. With the increase of the working frequency, the eddy current loss increases rapidly. The eddy current loss not only reduces the performance of the magnetic core, but also causes the device to heat. With the improvement of electronic technology, the requirements for the magnetic device are also higher and higher, mainly in the direction of miniaturization and high frequency, and higher requirements are put forward for the magnetic loss and temperature rise performance. In order to reduce the energy loss caused by the eddy current loss, it is critical to increase the resistivity of the magnetic core by reducing the electrical conductivity of the magnetic core. The common processing method is to perform insulation coating treatment on the surface of the magnetic core particles. The substances used for insulation coating treatment mainly include organic substances, inorganic substances and mixtures of the two. Common organic insulation coating agents mainly include epoxy resin, high-temperature-resistant silicone resin, phenolic resin and polypropylene silicone resin. The organic coating agent has strong fluidity and good coating and bonding capacity, the resistivity of the soft magnetic particles after coating is significantly improved, and the coating process is simple. However, the organic substance is volatile at high temperature, so the magnetic powder core prepared by the organic coating agent cannot be annealed at a high temperature, which also limits the application of the organic coating agent. Compared with the organic coating agent, the inorganic coating agent has high temperature resistance, and the prepared magnetic powder core can be annealed at a high temperature. However, the inorganic substance does not have bonding property, so the coating effect is not good, which affects the final performance of the magnetic powder core. Ferrite, silicate and various oxides with high resistivity (such as silicon dioxide, magnesium oxide, aluminum oxide, titanium oxide and other high-melting-point oxides) are often used as inorganic coating agents.

[0005] To achieve both good adhesion and high temperature resistance, existing methods generally use low-melting-point glass powder as the insulating medium. However, low-melting-point glass powder has a high magnetic dilution effect, which leads to a decrease in the magnetic permeability of the material. Furthermore, low-melting-point glass powder has poor interfacial compatibility with soft magnetic powder, making it prone to agglomeration and resulting in unsatisfactory coating effects. Summary of the Invention

[0006] In view of the shortcomings and deficiencies of the existing technology, the primary objective of this invention is to provide a method for preparing a FeSiAl magnetic powder core with high permeability and low loss.

[0007] Another object of the present invention is to provide a FeSiAl magnetic powder core prepared by the above method.

[0008] Another object of the present invention is to provide the application of the above-mentioned FeSiAl magnetic powder core in the fields of AI computing chips, servers and communication equipment.

[0009] The objective of this invention is achieved through the following technical solution:

[0010] A method for preparing a high-permeability, low-loss FeSiAl magnetic powder core includes the following steps:

[0011] (1) Mix pure Al powder with organosilicon sol, aluminate coupling agent, lubricant and organic binder evenly to obtain a coating adhesive slurry;

[0012] (2) Mix the FeSiAl soft magnetic powder with the coating adhesive slurry in step (1) evenly, first hot press and solidify it under a temperature of 60~100℃ and a vacuum condition, and then hot press and sinter it under a temperature of 750~1000℃ and an oxygen-containing atmosphere to obtain a high permeability and low loss FeSiAl magnetic powder core.

[0013] Furthermore, the average particle size of the pure Al powder in step (1) is 0.2~5μm.

[0014] Further, the organosilicon sol mentioned in step (1) is an organosilicon sol with a solid content of 20-40% and a solvent of ethyl acetate, cyclohexanone, propylene glycol methyl ether acetate, methyl ethyl ketone or methyl isobutyl ketone.

[0015] Further, the lubricant mentioned in step (1) is zinc stearate, magnesium stearate or polyvinyl ether.

[0016] Further, the organic binder in step (1) is an epoxy resin, acrylic resin or organosilicon resin with a solid content of 20-40% and a diluent of ethyl acetate, cyclohexanone, propylene glycol methyl ether acetate, toluene or xylene.

[0017] Further, the mass ratio of the pure Al powder mixed with the organosilicon sol, aluminate coupling agent, lubricant and organic binder in step (1) is (30~60):100:(2~5):(2~5):(30~60).

[0018] Furthermore, the FeSiAl soft magnetic powder in step (2) has a particle size of 1~50μm.

[0019] Further, the mass of the coating adhesive slurry in step (2) is 1 to 10% of the mass of the FeSiAl soft magnetic powder.

[0020] Furthermore, the pressure for hot pressing and curing in step (2) is 100~300MPa, and the time is 2~6h.

[0021] Further, the oxygen-containing atmosphere mentioned in step (2) is an air atmosphere or a mixed atmosphere of oxygen and argon.

[0022] Furthermore, the pressure of the hot pressing sintering process in step (2) is 500~800MPa, and the time is 10~90min.

[0023] A high-permeability, low-loss FeSiAl magnetic powder core was prepared by the above method.

[0024] The above-mentioned FeSiAl magnetic powder cores are used in AI computing chips, servers, and communication equipment.

[0025] The principle of this invention is as follows: A coating adhesive slurry is prepared using low-melting-point pure Al powder, organosilicon sol, aluminate coupling agent, lubricant, and organic binder. The aluminate coupling agent and lubricant help improve the dispersion compatibility of the pure Al powder with the organosilicon sol and organic binder, thereby improving the coating uniformity. Then, it is cured by hot pressing under vacuum conditions, removing the solvent and oxygen from the matrix while improving the adhesion and density of each component, forming a uniform SiO2 insulating coating base layer. Next, hot pressing sintering is performed at 750~1000℃ in an oxygen-containing atmosphere. The thermal decomposition of the aluminate coupling agent, lubricant, and organic binder creates air gaps in the SiO2 insulating coating base layer. The Al powder melts and fills these gaps under pressure. Simultaneously, the oxygen in the oxygen-containing atmosphere directionally oxidizes the filled Al liquid in situ through these gaps, thus forming a highly adhesive and highly stable alumina-SiO2 composite insulating coating layer.

[0026] Compared with the prior art, the beneficial effects of the present invention are:

[0027] (1) The present invention uses low-melting-point pure Al powder with organosilicon sol, aluminate coupling agent, lubricant and organic binder to prepare coating adhesive slurry, which has good adhesion to soft magnetic powder and good coating uniformity; at the same time, the low-melting-point pure Al powder is melted at high temperature to fill the air gap generated by the thermal decomposition of organic materials and oxidized in situ to form an oxide insulating layer, which can significantly improve the material density and improve the insulation coating effect.

[0028] (2) The composite insulating coating layer of the present invention has better bonding performance and lower magnetic dilution effect than existing low melting point glass powder, and the resulting magnetic powder core has higher magnetic permeability.

[0029] (3) By first hot-pressing and curing the mold under vacuum conditions, the oxygen content in the matrix can be reduced, thereby reducing the oxidation of the FeSiAl soft magnetic powder matrix inside the magnetic powder core during the subsequent high-temperature sintering process. This allows the oxidation reaction during the hot-pressing and sintering process to be concentrated in the air gap generated by the decomposition of organic materials, thereby achieving in-situ directional oxidation of the Al liquid filling. This improves the insulation coating effect while also reducing the adverse effect of the oxidation of the FeSiAl soft magnetic powder matrix on the permeability. Detailed Implementation

[0030] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto.

[0031] Example 1

[0032] A method for preparing a high-permeability, low-loss FeSiAl magnetic powder core includes the following steps:

[0033] (1) Pure Al powder with an average particle size of 3 μm is mixed evenly with organosilicon sol (solid content of 30%, solvent is methyl ethyl ketone), aluminate coupling agent DL-411, polyvinyl isobutyl ether and epoxy resin binder (solid content of 30%, dilution solvent is ethyl acetate) in a mass ratio of 45:100:4:3:50 to obtain a coating adhesive slurry.

[0034] (2) FeSiAl soft magnetic powder with an average particle size of 20μm is mixed with the coating adhesive slurry of step (1) at a mass ratio of 100:7. It is first hot-pressed for 4 hours under the conditions of 80℃ temperature, 300MPa pressure and vacuum to solidify and form the core. Then, it is hot-pressed and sintered for 30 minutes under the conditions of 850℃ temperature, 700MPa pressure and O2 (10vt%) / Ar2 mixed atmosphere to obtain a high permeability and low loss FeSiAl magnetic powder core.

[0035] The FeSiAl magnetic powder core obtained in this embodiment has a tested permeability (1MHz / 30mT) of 91.2 and a high-frequency loss (1MHz / 30mT) of 753kW / m. 3 .

[0036] Example 2

[0037] A method for preparing a high-permeability, low-loss FeSiAl magnetic powder core includes the following steps:

[0038] (1) Pure Al powder with an average particle size of 3 μm is mixed evenly with organosilicon sol (solid content of 30%, solvent is methyl ethyl ketone), aluminate coupling agent DL-411, zinc stearate and epoxy resin binder (solid content of 30%, dilution solvent is ethyl acetate) in a mass ratio of 40:100:3:3:50 to obtain a coating adhesive slurry.

[0039] (2) FeSiAl soft magnetic powder with an average particle size of 20μm is mixed with the coating adhesive slurry in step (1) at a mass ratio of 100:6. It is first hot-pressed for 5h at 80℃, 200MPa and vacuum conditions to solidify and form the core. Then, it is hot-pressed and sintered for 60min at 800℃, 600MPa and O2 (10vt%) / Ar2 mixed atmosphere to obtain a high permeability and low loss FeSiAl magnetic powder core.

[0040] The FeSiAl magnetic powder core obtained in this embodiment has a tested permeability (1MHz / 30mT) of 96.7 and a high-frequency loss (1MHz / 30mT) of 849kW / m. 3 .

[0041] Example 3

[0042] A method for preparing a high-permeability, low-loss FeSiAl magnetic powder core includes the following steps:

[0043] (1) Pure Al powder with an average particle size of 3 μm is mixed with organosilicon sol (solid content of 30%, solvent is methyl ethyl ketone), aluminate coupling agent DL-411, magnesium stearate and epoxy resin binder (solid content of 30%, dilution solvent is ethyl acetate) in a mass ratio of 30:100:3:2:40 to obtain a coating adhesive slurry.

[0044] (2) FeSiAl soft magnetic powder with an average particle size of 20μm is mixed with the coating adhesive slurry of step (1) at a mass ratio of 100:5. It is first hot-pressed for 6 hours under the conditions of 80℃ temperature, 100MPa pressure and vacuum to solidify and form the core. Then, it is hot-pressed and sintered for 40 minutes under the conditions of 900℃ temperature, 500MPa pressure and O2 (10vt%) / Ar2 mixed atmosphere to obtain a high permeability and low loss FeSiAl magnetic powder core.

[0045] The FeSiAl magnetic powder core obtained in this embodiment has a tested permeability (1MHz / 30mT) of 102.4 and a high-frequency loss (1MHz / 30mT) of 866kW / m. 3 .

[0046] Example 4

[0047] A method for preparing a high-permeability, low-loss FeSiAl magnetic powder core includes the following steps:

[0048] (1) Pure Al powder with an average particle size of 3 μm is mixed evenly with organosilicon sol (solid content of 30%, solvent is methyl ethyl ketone), aluminate coupling agent DL-411, zinc stearate and epoxy resin binder (solid content of 30%, dilution solvent is ethyl acetate) in a mass ratio of 50:100:4:4:50 to obtain a coating adhesive slurry.

[0049] (2) The FeSiAl soft magnetic powder with an average particle size of 20μm is mixed with the coating adhesive slurry of step (1) at a mass ratio of 100:4. It is first hot-pressed for 3h under the conditions of 80℃ temperature, 100MPa pressure and vacuum to solidify and form the core. Then, it is hot-pressed and sintered for 30min under the conditions of 800℃ temperature, 800MPa pressure and O2 (10vt%) / Ar2 mixed atmosphere to obtain a high permeability and low loss FeSiAl magnetic powder core.

[0050] The FeSiAl magnetic powder core obtained in this embodiment has a tested permeability (1MHz / 30mT) of 110.6 and a high-frequency loss (1MHz / 30mT) of 937kW / m. 3 .

[0051] Example 5

[0052] A method for preparing a high-permeability, low-loss FeSiAl magnetic powder core includes the following steps:

[0053] (1) Pure Al powder with an average particle size of 3 μm is mixed with organosilicon sol (solid content of 30%, solvent is methyl ethyl ketone), aluminate coupling agent DL-411, zinc stearate and epoxy resin binder (solid content of 30%, dilution solvent is ethyl acetate) in a mass ratio of 60:100:5:5:60 to obtain a coating adhesive slurry.

[0054] (2) The FeSiAl soft magnetic powder with an average particle size of 20μm is mixed with the coating adhesive slurry of step (1) at a mass ratio of 100:8. It is first hot-pressed for 2 hours under the conditions of 80℃ temperature, 300MPa pressure and vacuum to solidify and form the core. Then, it is hot-pressed and sintered for 10 minutes under the conditions of 1000℃ temperature, 500MPa pressure and O2 (10vt%) / Ar2 mixed atmosphere to obtain a high permeability and low loss FeSiAl magnetic powder core.

[0055] The FeSiAl magnetic powder core obtained in this embodiment has a tested permeability (1MHz / 30mT) of 88.3 and a high-frequency loss (1MHz / 30mT) of 756kW / m. 3 .

[0056] Comparative Example 1

[0057] A method for preparing FeSiAl magnetic powder core, compared with Example 1, is that pure Al powder is not added to the coating adhesive slurry in step (1), but the rest are the same.

[0058] The soft magnetic powder material obtained in this comparative example has a tested permeability (1MHz / 30mT) of 65.3 and a high-frequency loss (1MHz / 30mT) of 1425kW / m. 3 .

[0059] The comparison results with Example 1 show that when pure Al powder with low melting point is not added, the magnetic permeability of the resulting magnetic powder core is significantly reduced and the high-frequency loss is significantly increased.

[0060] Comparative Example 2

[0061] A method for preparing FeSiAl magnetic powder cores, compared with Example 1, uses an equal amount of Al2O3 powder with an average particle size of 3μm to replace pure Al powder, while the rest are the same.

[0062] The soft magnetic powder material obtained in this comparative example has a tested permeability (1MHz / 30mT) of 62.6 and a high-frequency loss (1MHz / 30mT) of 1687kW / m. 3 .

[0063] The comparison results with Example 1 show that the uniformity of Al2O3 powder coating is poor and it cannot effectively fill the air gap, resulting in a significant decrease in the permeability of the magnetic powder core and a significant increase in high-frequency loss.

[0064] Comparative Example 3

[0065] A method for preparing FeSiAl magnetic powder cores, compared with Example 1, uses commercially available low-melting-point glass powder (melting temperature 550℃) instead of the combination of pure Al powder and organosilicon sol. The specific preparation steps are as follows:

[0066] (1) Mix low melting point glass powder with aluminate coupling agent DL-411, polyvinyl isobutyl ether and epoxy resin binder (solid content is 30%, dilution solvent is ethyl acetate) in a mass ratio of 75:4:3:50 to obtain a coating adhesive slurry.

[0067] (2) The FeSiAl soft magnetic powder with an average particle size of 20μm is mixed with the coating adhesive slurry of step (1) at a mass ratio of 100:7. The mixture is first hot-pressed for 4 hours at 80℃, 300MPa and vacuum conditions to solidify the core. Then, it is hot-pressed and sintered for 30 minutes at 850℃, 700MPa and O2 (10vt%) / Ar2 mixed atmosphere to obtain the FeSiAl magnetic powder core.

[0068] The FeSiAl magnetic powder core obtained in this comparative example has a tested permeability (1MHz / 30mT) of 70.8 and a high-frequency loss (1MHz / 30mT) of 772kW / m. 3 .

[0069] The comparison results with Example 1 show that although the combination of low melting point glass powder and organic binder can achieve better insulation coating and reduce high frequency loss, it will lead to a significant reduction in magnetic permeability.

[0070] Comparative Example 4

[0071] A method for preparing FeSiAl magnetic powder cores, compared with Example 1, involves hot-pressing curing under conventional air conditions. The specific preparation steps are as follows:

[0072] Step (1) is the same as in Example 1.

[0073] (2) The FeSiAl soft magnetic powder with an average particle size of 20μm is mixed with the coating adhesive slurry of step (1) at a mass ratio of 100:7. The mixture is first hot-pressed for 4 hours at 80℃, 300MPa pressure and air to solidify the core. Then, it is hot-pressed and sintered for 30 minutes at 850℃, 700MPa pressure and O2 (10vt%) / Ar2 mixed atmosphere to obtain the FeSiAl magnetic powder core.

[0074] The FeSiAl magnetic powder core obtained in this embodiment has a tested permeability (1MHz / 30mT) of 45.9 and a high-frequency loss (1MHz / 30mT) of 615kW / m. 3 .

[0075] The comparison results with Example 1 show that the FeSiAl soft magnetic powder matrix obtained by not hot-pressing and curing under vacuum conditions before sintering has a high oxygen content, which leads to excessive oxidation inside the FeSiAl soft magnetic powder and a significant decrease in the permeability of the resulting magnetic powder core.

[0076] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a high-permeability, low-loss FeSiAl magnetic powder core, characterized in that: Includes the following steps: (1) Mix pure Al powder with organosilicon sol, aluminate coupling agent, lubricant and organic binder evenly to obtain a coating adhesive slurry; (2) Mix the FeSiAl soft magnetic powder with the coating adhesive slurry in step (1) evenly, first hot press and solidify it under a temperature of 60~100℃ and a vacuum condition, and then hot press and sinter it under a temperature of 750~1000℃ and an oxygen-containing atmosphere to obtain a high permeability and low loss FeSiAl magnetic powder core.

2. The method for preparing a high-permeability, low-loss FeSiAl magnetic powder core according to claim 1, characterized in that: The average particle size of the pure Al powder in step (1) is 0.2~5μm.

3. The method for preparing a high-permeability, low-loss FeSiAl magnetic powder core according to claim 1, characterized in that: The organosilicon sol in step (1) has a solid content of 20-40% and uses ethyl acetate, cyclohexanone, propylene glycol methyl ether acetate, methyl ethyl ketone or methyl isobutyl ketone as solvent; the lubricant is zinc stearate, magnesium stearate or polyethylene ether; the organic binder has a solid content of 20-40% and uses epoxy resin, acrylic resin or organosilicon resin as diluent, ethyl acetate, cyclohexanone, propylene glycol methyl ether acetate, toluene or xylene as diluent.

4. The method for preparing a high-permeability, low-loss FeSiAl magnetic powder core according to claim 1, characterized in that: The mass ratio of the pure Al powder mixed with organosilicon sol, aluminate coupling agent, lubricant and organic binder in step (1) is (30~60):100:(2~5):(2~5):(30~60).

5. The method for preparing a high-permeability, low-loss FeSiAl magnetic powder core according to claim 1, characterized in that: The FeSiAl soft magnetic powder mentioned in step (2) has a particle size of 1~50μm.

6. The method for preparing a high-permeability, low-loss FeSiAl magnetic powder core according to claim 1, characterized in that: The mass of the coating adhesive slurry mentioned in step (2) is 1 to 10% of the mass of the FeSiAl soft magnetic powder.

7. The method for preparing a high-permeability, low-loss FeSiAl magnetic powder core according to claim 1, characterized in that: The pressure for hot pressing and curing in step (2) is 100~300MPa, and the time is 2~6h.

8. The method for preparing a high-permeability, low-loss FeSiAl magnetic powder core according to claim 1, characterized in that: The oxygen-containing atmosphere mentioned in step (2) is an air atmosphere or a mixture of oxygen and argon; the pressure of the hot pressing sintering treatment is 500~800MPa and the time is 10~90min.

9. A high-permeability, low-loss FeSiAl magnetic powder core, characterized in that: It is prepared by the method described in any one of claims 1 to 8.

10. The application of the FeSiAl magnetic powder core according to claim 9 in the fields of AI computing chips, servers and communication equipment.

Citation Information

Patent Citations

  • Limited-range insulation coating soft magnet silicon-aluminum process and product thereof

    CN114373621A

  • Preparation method of high-temperature-resistant metal soft magnetic composite material

    CN116037914A

  • FeSiAl soft magnetic composite material and preparation method thereof

    CN120998620A

  • Dust core

    JP2013098384A

Cited By

  • A core-shell structure FeSi / CIP@SiO2 soft magnetic composite material and a preparation method thereof

    CN122474446A